Nowe spojrzenie na koncepcję uniwersytetu Johna Henry’ego Newmana - Obirek, Stanisław (Człowiek i Społeczeństwo, 2021)
The article presents the concept of the university developed in the mid-nineteenth century by Cardinal John Henry Newman. Newman believed that the university should provide pure and universal knowledge. He was against the professionalization of academic education. According to Newman, the task of universities was to “introduce to life in society” and to “adapt to the world.” This idea grew out of European optimism and a deep belief that teachers and students were part of the same intellectual community. Newman’s concept retains its value because it is rooted in the legacy of humanistic ideal of the education present in the university from very beginnings of this institution. As we know from history university was a place for gaining universal knowledge. However, disturbing cracks can be seen in this idea, which is related to the commercialization and parameterization of the education process. Both lead to deep pathologies of academic life. We see these changes not only in Poland, but also in Western Europe and the United States. After the change of the political system in 1989, Polish universities were significantly degraded and the status of an academic teacher decreased dramatically. The only remedy is to restore universities to the autonomy they deserve and to move away from attempts to politicize or ideologize them